1998
DOI: 10.1111/j.1469-7998.1998.tb00054.x
|View full text |Cite
|
Sign up to set email alerts
|

A population study of the dicrocoeliid trematode Paradistomum orientalis in the garden lizard Calotes versicolor

Abstract: The population biology of Paradistomum orientalis, a dicrocoeliid trematode occurring in the gall bladder of the garden lizard Calotes versicolor, was investigated during 1991±1993. The prevalence and abundance of the¯uke were high throughout the year and demonstrated no seasonal¯uctuations. The maturation cycle of the¯uke followed an annual pattern. The recruitment of the¯uke was restricted to the period September to February, with a peak during September. Mature¯ukes occurred throughout the year, facilitatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…For example, rainfall is a major factor in determining trematode abundance in the garden lizard Calotes versicolor as it regulates the population of snails that serve as the first intermediate host and produce infectious stages (Madhavi, Nirmala, & Subbalakshmi, 1998). Biserkov and Kostadinova (1998) found that Lacerta viridis (European green lizard) living in habitats with permanent water bodies harboured trematodes, whereas those living in drier habitats did not.…”
Section: Discussionmentioning
confidence: 99%
“…For example, rainfall is a major factor in determining trematode abundance in the garden lizard Calotes versicolor as it regulates the population of snails that serve as the first intermediate host and produce infectious stages (Madhavi, Nirmala, & Subbalakshmi, 1998). Biserkov and Kostadinova (1998) found that Lacerta viridis (European green lizard) living in habitats with permanent water bodies harboured trematodes, whereas those living in drier habitats did not.…”
Section: Discussionmentioning
confidence: 99%